Clinical impact of cardiovascular magnetic resonance with optimized myocardial scar detection in patients with cardiac implantable devices. (15th March 2019) - Bhuva, Anish N.; Kellman, Peter; Graham, Adam; Ramlall, Manish; Boubertakh, Redha; Feuchter, Patricia; Hawkins, Angela; Lowe, Martin; Lambiase, Pier D.; Sekhri, Neha; Schilling, Richard J.; Moon, James C.; et al.
Abstract: Background: Myocardial scar assessment using late gadolinium enhancement Cardiovascular Magnetic Resonance (LGE CMR) is commonly indicated for patients with cardiac implantable electronic devices (CIEDs), however metal artifact can degrade images. We evaluated the clinical impact of LGE CMR incorporating a device-dependent metal artifact reduction strategy in patients with CIEDs. Methods: 136 CMR studies were performed in 133 consecutive patients (age 56 ± 19 years, 69% male) with CIEDs (22% implantable loop recorders [ILRs], 40% permanent pacemakers [PPMs], 38% implantable cardioverter defibrillators [ICDs]; 42% non-MRI conditional) over 2 years, without complication. LGE imaging was tailored to the CIED, using a wideband sequence for left-sided PPMs and ICDs and conventional sequences for ILRs and right-sided PPMs, scoring segmental artifact. Diagnostic utility and impact on clinical management were scored by consensus of experts. Results: CMR provided unexpected diagnoses in 22 (16%) and changed management in 113 (83%) patients. Myocardial scar was present in 92 (68%), with other abnormalities detected in another 13%. Using conventional LGE, 43 (32%) studies were non-diagnostic (79% of defibrillators) compared to 0% using wideband LGE imaging. Wideband LGE results changed clinical management in an additional 39 (75%) defibrillator patients and 10 (19%) pacemaker patients when compared to imaging with conventional LGE sequences. Conclusion: The clinical yield from CMR using optimized LGE sequences in patients with CIEDs is high with no demonstrated clinical risk. A device-dependent LGE imaging strategy using wideband LGE is needed to achieve clinical utility especially in ICD recipients. Highlights: CMR with myocardial scar assessment has clinical impact in 83% cardiac device patients, without risk. A device-dependent strategy for scar imaging should be used to optimize image quality. Wideband scar imaging improves image quality and so clinical utility in 75% ICD and 19% PPM patients. Conventional scar imaging is appropriate for ILRs and right-sided PPMs.